AWF Project in MLW Watershed, DRC Yamboyo LDSF Site: soil health results - Winowiecki, Leigh Ann; Vågen, Tor-Gunnar (2014)
The Maringa-Lopori-Wamba Landscape (MLW) in DRC encompasses a wide range of land cover types, including dense moist semi-deciduous alongside smallholder agricultural systems. Regional interventions aimed to increase productivity was conserving natural resources have lacked baseline information on soil and land health for making informed decisions. This initiative aimed to fill gaps related to biophysical constraints in order to inform decisions.